2022
DOI: 10.3389/fphar.2022.763608
|View full text |Cite
|
Sign up to set email alerts
|

Amentoflavone Ameliorates Carrageenan-Induced Pleurisy and Lung Injury by Inhibiting the NF-κB/STAT3 Pathways via Nrf2 Activation

Abstract: Many natural flavonoids can activate nuclear factor erythroid 2-related factor 2 (Nrf2), which is pivotal for alleviating various diseases related to inflammation and oxidative stress, including pleurisy. Amentoflavone (AMF), a biflavonoid extracted from many plants, has some beneficial bioactivities, especially anti-inflammatory and antioxidative activities. We aimed to investigate whether AMF protects against pleurisy and lung injury induced by carrageenan (Car) by activating Nrf2. Pleurisy was induced in wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 30 publications
1
0
0
Order By: Relevance
“…Persistently activated STAT3 is associated with the proliferation, survival, and invasiveness of tumor cells, including those of breast, lung, pancreatic, and head and neck origin. Recent studies suggested the possibility of the interplay or cross talk between Nrf2 and STAT3 [40,41]. In our studies, RT restrained the phosphorylation of STAT3 and decreased Nrf2 in protein levels, suggesting that the STAT3/Nrf-2 signaling axis might be involved in the mechanism of RT repressing migration and invasion.…”
Section: Discussionsupporting
confidence: 64%
“…Persistently activated STAT3 is associated with the proliferation, survival, and invasiveness of tumor cells, including those of breast, lung, pancreatic, and head and neck origin. Recent studies suggested the possibility of the interplay or cross talk between Nrf2 and STAT3 [40,41]. In our studies, RT restrained the phosphorylation of STAT3 and decreased Nrf2 in protein levels, suggesting that the STAT3/Nrf-2 signaling axis might be involved in the mechanism of RT repressing migration and invasion.…”
Section: Discussionsupporting
confidence: 64%
“…Interestingly, these characteristic effects of SIRT1 inhibition by CPA were dose-dependently mitigated in the present work with the administration of AMV. These favorable effects may be attributed to the ability of AMV to increase the genetic expression of SIRT1 with a subsequent increase in Nrf2 content in the pulmonary tissues, which restores the prooxidant/antioxidant balance to normal values [16,42]. In addition, the enhancement of the histone deacetylase activity of SIRT1 mediated by AMV may underlie the mitigating effects of AMV detected in the present study on the inflammatory cascade [16,43].…”
Section: Discussionmentioning
confidence: 89%
“…By combining diferent in vivo and in vitro models (Tables 2 and 3), a study indicates that extracts obtained from A. corniculatum, specifcally methanol and ethyl acetate extracts, exhibit notable inhibitory efects on the chronic infammatory phase and these efects are observed through the suppression of mononuclear cell infltration, fbroblast proliferation, collagen fber production, and connective tissue formation, all of which contribute to the development of granuloma [45]. Carrageenan-induced pleurisy is a very common method used to test anti-infammatory therapeutics [49]. Methanol and ethyl acetate extract of A. corniculatum protects against acute lung infammation by lowering nitrate/nitrite concentrations and MPO enzyme levels and also decreases neutrophils and mononuclear infltration at a higher dose (100 mg/kg) in a mice model of pleurisy [47] (Table 3).…”
Section: Anti-infammatorymentioning
confidence: 99%